Level of knowledge about Sexually Transmitted Infections Sexually Transmitted Infections among medical students at the Universidad Abierta Interamericana - Sede Rosario, year 2022 - Rossi, Agustina; Gustafsson, Dra. Mónica; Tomarchio, Dra. Daniela (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Sexually transmitted infections (STIs) encompass a set of pathologies, belonging to different infectious etiologies, spread predominantly by sexual contact, whether vaginal, anal or oral sex. Young adults are part of the most vulnerable population where it is essential to strengthen prevention, awareness and education actions. Objective: To describe the level of knowledge about sexually transmitted infections in first year medical students of the Universidad Abierta Interamericana - Sede Rosario, 2022. Materials and methods: A quantitative, descriptive, observational, cross-sectional, prospective, quantitative study. Carried out at the Universidad Abierta Interamericana, Rosario campus. The population consisted of all 1st year students belonging to the School of Medicine and Health Sciences. The sampling was non-probabilistic by convenience. The data collection instrument consisted of an anonymous, voluntary and self-administered survey made up of 23 closed, multiple-choice questions with which the variables age, sex and level of knowledge were re-evaluated. The variables were analyzed through absolute and relative percentage frequencies and summarized through central position measures: mean, median and mode and dispersion measures: range and standard deviation. Results: A total of 178 students were surveyed, 100% of the students were in the 1st year of the course, with a mean age of 22.44 ± 4.40 years (min. 18; max. 48), of whom 116 (65%) were female and 62 (35%) were male. 97 (54%) students were not taking any STI-related subjects, 56 (32%) were taking one subject, 21 (12%) were taking two subjects and 4 (2%) were taking 4 subjects. The mean score was 13.64 ± 3.38 (min. 5; max. 20). 38% (67) of the students possessed a high level of knowledge about STIs, 40% (71) medium knowledge and 22% (40) low knowledge about STIs. Conclusions: Students have a medium-high level of knowledge about sexually transmitted infections in relation to definitions, forms of transmission and laboratory tests for the diagnosis of STIs and HIV. However, they present low knowledge regarding pathogens, clinical manifestations, treatment and complications of STIs